Cpd-42 protects against calcium oxalate nephrocalcinosis-induced renal injury and inflammation by targeting RIPK3-mediated necroptosis - Hou, Bingbing; Liu, Mingming; Chen, Yang; Ni, Weijian; Suo, Xiaoguo; Xu, Yuexian; He, Qiushi; Meng, Xiaoming; Hao, Zongyao (Frontiers in Pharmacology, 2022)
Calcium oxalate (CaOx) crystals, as the predominant component of human kidney stones, can trigger excessive cell death and inflammation of renal tubular epithelial cells, involved in the pathogenesis of nephrocalcinosis. Necroptosis mediated by receptor-interacting protein kinase 3 (RIPK3) serves a critical role in the cytotoxicity of CaOx crystals. Here, we report a novel RIPK3 inhibitor, compound 42 (Cpd-42), and assessed its therapeutic potential for CaOx nephrocalcinosis by comparison with dabrafenib, a classic RIPK3 inhibitor. Our results demonstrated that Cpd-42 pretreatment attenuated CaOx crystals-induced renal tubular epithelial cell (TEC) injury by inhibiting necroptosis and inflammation in vitro and in vivo. Furthermore, in an established mouse model of CaOx nephrocalcinosis, Cpd-42 also restored renal injury while improving the impaired kidney function and intrarenal crystal deposition. Consistent with this finding, Cpd-42 was confirmed to exhibit superior inhibition of necroptosis and protection against renal TEC injury compared to the classic RIPK3 inhibitor darafenib in vitro and in vivo. Mechanistically, RIPK3 knockout (KO) tubular epithelial cells pretreated with Cpd-42 did not show further enhancement of the protective effect on crystals-induced cell injury and inflammation. We confirmed that Cpd-42 exerted protective effects by specifically targeting and inhibiting RIPK3-mediated necroptosis to block the formation of the RIPK1-RIPK3 necrosome. Taken together, targeted inhibition of RIPK3-mediated necroptosis with Cpd-42 may provide a potential therapeutic approach for CaOx nephrocalcinosis.